332 The Relationship Between Rapid Fluctuation in Serum Sodium and Intraventricular Hemorrhage (IVH) in Hypernatremic Extremely Low Birth Weight Preterm Infants. (October 2012) - Sarkar, S; Dalton, J; Dechert, R
Abstract : Hypernatremia causes brain shrinkage and resultant vascular rupture with cerebral and IVH. However, it is not known if rapid fluctuation in serum sodium in hypernatremic preterm infants results in IVH or death. Objective: To determine if the rapid rise in serum sodium or rapid correction of hypernatremia predict the composite outcome of severe IVH (grade 3 and 4) or death during the first 10 days of life. Methods: Single center retrospective review of 167 preterm infants with GA ≤26 weeks who had serum sodium monitored at least every 12–24 hours and more frequently, if indicated. Logistic regression analysis identified which of the commonly cited risk factors of IVH, including rapid (>10 and >15 mmol/l/day) rise or fall in serum sodium could predict composite outcome in hypernatremic infants. Results: 98 (59%) of 167 infants studied developed hypernatremia (serum sodium>150 mmol/L), with a maximum median serum sodium of 154 mmol/l (range 150–181, IQR 152–157), occurring on median postnatal age of 4 days (IQR 3–5). Grade 4 IVH was more frequent in hypernatremic compared to normonatremic infants (p=0.032, OR 3.4, 95% CI 1.1–10.6). Among 98 infants with hypernatremia, severe IVH or death occurred in 33 and 21 infants with rapid (>10 mmol/l/day) rise and drop in serum sodium, respectively. However, rapid (>10 and >15 mmol/l/day) rise or fall in serum sodium was not associated with composite outcome on multivariate analysis. Conclusion: Correction of hypernatremia not exceeding 10 to 15 mmol/l/day in hypernatremic preterm infants was not associated with severe IVH or death.